Increased risk for renal cell carcinoma in end stage renal disease – a population-based case-control study. (4th May 2021) - Åkerlund, John; Holmberg, Erik; Lindblad, Per; Stendahl, Maria; Ljungberg, Börje; Thorstenson, Andreas; Lundstam, Sven
Abstract: Purpose: End-stage renal disease (ESRD) is a known risk factor for the development of renal cell carcinoma (RCC). This case-control study was performed to assess the risk in a nationwide cohort and evaluate tumor characteristics and survival in the ESRD-RCC population. Methods: In this study, 9, 299 patients with RCC identified in the National Swedish Kidney Cancer Register from 2005 until 2014 and 93, 895 matched controls were linked to the Swedish Renal Registry and the National Patient Register. ESRD was defined as chronic kidney disease stage 5, kidney transplantation or kidney dialysis 0–40 years before the diagnosis of RCC. Results: A total of 117 patients with ESRD and subsequent RCC were identified and compared with 9, 087 patients with RCC. There was a 4.5-times increased risk for RCC among ESRD patients (95% CI = 3.6–5.6; p < 0.001) compared to matched controls. Longer time with ESRD increased the risk of RCC (ESRD > 9 years, OR = 10.2, 95% CI = 7.0–14.8). The ESRD-RCC patients were younger ( p = 0.002), had smaller tumors ( p < 0.001) and had lower tumor stage ( p = 0.045). The incidence of papillary and chromophobe RCC was higher and clear cell RCC lower among the ESRD patients ( p < 0.001). The 5-year overall survival was 50% in ESRD-RCC patients and 63% in RCC-only patients ( p < 0.05). Conclusion: More than 9 years with ESRD increased the risk of developing RCC 10-times compared to individuals without ESRD and the tumors showed a different histopathological pattern. Despite a less advanced tumor stage at diagnosis, the overall survival in ESRD-RCC patients was lower compared to patients with RCC-only.